WEB SERIES SEBAGAI KOMUNIKASI PEMASARAN DIGITAL TRAVELOKA - Radja Erland Hamzah (Universitas Prof. Dr. Moestopo (Beragama), 2018)
Web series is a concept of a series of programs released in the medium of the Internet, usually Youtube become the main platform for the producers of the web series. Then in the process of digital promotion, Traveloka optimize the form of web content series with the theme